CONDITIONS FOR EXACT CAVALIERI ESTIMATION - Tinajero-Bravo, Mónica; Eslava-Gómez, Guillermina; Cruz-Orive, Luis Manuel (Image Analysis and Stereology, 2014)
Exact Cavalieri estimation amounts to zero variance estimation of an integral with systematic observations along a sampling axis. A sufficient condition is given, both in the continuous and the discrete cases, for exact Cavalieri sampling. The conclusions suggest improvements on the current stereological application of fractionator-type sampling.